2014
DOI: 10.2485/jhtb.23.15
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Apatite Precipitation on an Alkaline Hydrolyzed Poly (Lactic acid-ε-Caprolactone) Film in Simulated Body Fluid

Abstract: Biodegradable materials, such as poly (lactic acid) (PLA), have been applied to regenerate bone. However, pure PLA is brittle, so it can be modified by blending -caprolactone (PCL). These biodegradable materials have no known functional activity. In the present study, a copolymer of PLA/PCL (PLCL) film was fabricated by dissolving the materials in chloroform. Carboxylic acid groups (COOH) of PLCL were chemically introduced onto the PLCL film surface by 0.5N NaOH hydrolysis. Apatite formation was evaluated on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The PLCL50 -COOH films indicated a greater amount of precipitation than the PLCL50 films at 3 and 7 days. This result was agree with studies by Tsurumi et al (17) . They suggested that the surface carboxylic groups on the film that were introduced by NaOH treatment promoted apatite precipitation.…”
Section: Discussionsupporting
confidence: 94%
“…The PLCL50 -COOH films indicated a greater amount of precipitation than the PLCL50 films at 3 and 7 days. This result was agree with studies by Tsurumi et al (17) . They suggested that the surface carboxylic groups on the film that were introduced by NaOH treatment promoted apatite precipitation.…”
Section: Discussionsupporting
confidence: 94%
“…When the solution's pH increased to 13, weight losses were increased to 4.62%, 9.93%, 80.21%, and 62.16% furtherly. The main reason for this phenomenon was that the ester bond of PBS was easier hydrolyzed in an alkaline solution 40 . In addition, the weight loss of A5 and A0′ was higher than A0 and A2 because the foaming structure enlarged surface area .…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for this phenomenon was that the ester bond of PBS was easier hydrolyzed in an alkaline solution. 40 In addition, the weight loss of A5 and A0 0 was higher than A0 and A2 because the foaming structure enlarged surface area .41,42 The weight loss of A5 was higher than A0', and the weight loss of A2 was higher than A0. These phenomena indicated that cross-linking structure did not effect on PBS ester bond degradation.…”
Section: Hydrolytic Degradationmentioning
confidence: 98%
“…One of them is an unexpected degradation time, which can cause brittleness of the scaffolds, even during culturing [ 59 ]. One example is PLA, which can be influenced by the use of a PLA copolymer with PCL or PEG and will affect the quality of the material [ 107 , 110 , 114 ]. Synthetic materials also lack desirable biological properties [ 115 ].…”
Section: Scaffold For Articular Cartilage Repair: Requirements Mamentioning
confidence: 99%